2022
DOI: 10.1039/d1ta09310j
|View full text |Cite
|
Sign up to set email alerts
|

Visible light-induced enhancement in the Seebeck coefficient of PEDOT:PSS composites with two-dimensional potassium poly-(heptazine imide)

Abstract: Thermoelectric (TE) materials are significant for sustainable development because they can used to directly harvest heat into electricity. Although it is well known that light exposure can affect the electrical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…3D), which is inconsistent with previous reports. 46 This may be due to the strong absorption of PEDOT:PSS under near-infrared light, which leads to an induced voltage generated under illumination.…”
Section: Resultsmentioning
confidence: 99%
“…3D), which is inconsistent with previous reports. 46 This may be due to the strong absorption of PEDOT:PSS under near-infrared light, which leads to an induced voltage generated under illumination.…”
Section: Resultsmentioning
confidence: 99%
“…The PEDOT:PSS film obtained higher induced voltage under illumination, which is inconsistent with previous reports. 29,53 On the one hand, it may be due to the strong absorption of near-infrared light by PEDOT:PSS, which leads to heating under illumination to generate voltage. On the other hand, the PEDOT:PSS film was prepared with EtOH as a diluent and a small amount of DMSO was added, resulting in a conformational change of PEDOT:PSS to improve conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Specifically, chemical doping can increase s but also can decrease S. In contrast, in light-induced doping, it was found that light can simultaneously increase the comprehensive TE performance parameters. 28,29 Light is often applied to increase electronic properties particularly the conductivity of semiconductors and the field of optoelectronics is a very interesting area. 30,31 Xu et al 32 found that light illumination can simultaneously increase S and s of MEH-PPV polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The monolayer nature of graphene and its high quality were determined by Raman spectroscopy with a 532 nm laser excitation, , exhibiting the characteristic “G” mode with a strong “2D” signature as seen in Figure c. Moreover, the absorption spectrum of a PEDOT:PSS film fabricated on a quartz substrate is shown in Figure d, suggesting its high transparency to the NIR light . Since the overall thickness of the PEDOT:PSS/graphene composite film is far less than the wavelength and the skin depth of incident THz waves, the composite film can be considered as an approximate monolayer conductive film for the analysis of THz-wave propagation. , …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the absorption spectrum of a PEDOT:PSS film fabricated on a quartz substrate is shown in Figure 1d, suggesting its high transparency to the NIR light. 40 Since the overall thickness of the PEDOT:PSS/graphene composite film is far less than the wavelength and the skin depth of incident THz waves, the composite film can be considered as an approximate monolayer conductive film for the analysis of THz-wave propagation. 14,41 To observe the actively omnidirectional broadband THz AR behavior, the prepared PPGS and the uncoated Si substrate as a reference were measured using terahertz time-domain spectroscopy (THz-TDS, frequency range: 0.1−3.0 THz), and the THz transmission and reflection measurements were performed for incidence angles ranging from 0 to 70°( different angles: 0, 35, 45, 60, 70°), as schematically shown in Figures 2 and S1.…”
Section: Resultsmentioning
confidence: 99%